Civil society as a culturological category - Kamenets, Aleksandr Vladlenovich (2021)
The study is devoted to the current problems of studying civil society by means of culturology. The processes of formation of civil society as a culturological category are highlighted; its place and role in social development, as well as various interpretations of this sociocultural phenomenon, are considered. A fairly unambiguous understanding of the prerequisites of citizenship in the context of political culture and the culture of social interaction is proposed. The main problem situations that hinder the development of the civic activity of the population and their overcoming using the possibilities of state cultural policy are highlighted. A significant place in the study is devoted to the potential of civil society as a sociocultural mechanism of the relationship between the state and society, the institutional reality of the “systemic world” and the culture of everyday life, formed mainly in the space of the “lifeworld”.The morphology of civil society as a specific social formation and its cultural potential, which is associated mainly with the implementation of axiological components in social and civic activity in modern society, are analyzed. It also compares the understanding of the civil society in Western countries and the Russian experience of civil life. Further prospects for the study of civil society are outlined in the direction of searching for a synthesis of Russian and foreign experience in the formation and development of civil culture.